A Comparison of Global Surface Air Temperature Over the Oceans Between CMIP5 Models and NCEP Reanalysis - Zhu, Xian; Dong, Tianyun; Zhao, Shanshan; He, Wenping (Frontiers in Environmental Science, 2021)
By utilizing 8 CMIP5 model outputs in historical experiment that simulated daily mean sea surface temperature (SST) and NCEP reanalysis data over 12 ocean basins around the world from 1960 to 2005, this paper evaluates the performance of CMIP5 models based on the detrended fluctuation analysis (DFA) method. The results of National Centers for Environmental Prediction (NCEP) data showed that the SST in most ocean basins of the world had long-range correlation (LRC) characteristics. The DFA values of the SST over ocean basins are large in the tropics and small in high latitudes. In spring and autumn, the zonal average DFA of SST are basically distributed symmetrically in the Northern and Southern Hemispheres. In summer, the zonal average values of DFA in the Northern Hemisphere are larger than those in the southern hemisphere, and vice versa in winter. The performance of HadGEM2-AO, CNRM-CM5 and IPSL-CM5A-MR are all relative well among the 8 models in simulating SST over most regions of the global ocean.